Tourism as a tool for improving global education and international cooperation - Zhubi, Mimoza; Zhubi, Dren; Kovaçi, Idriz; Tahiri, Alberta (Edelweiss Applied Science and Technology, 2024)
The purpose of this paper is to assess the importance of tourism as a tool for improving global education and international cooperation. As a global economic phenomenon, tourism is one of the industries that contribute the most economic growth and the development of the world economy, where it also enables international cooperation by developing tourism and various activities at the global level. Tourism constitutes an important and influential sector of the economy, creating multiple uses and benefits. This sector, among other things, creates income, creates new jobs, influences the creation of international relations. The method. The empirical research was carried out on the basis of literature reviews by observing and analyzing the existing literature on the theory of sustainable tourism in the context of tourism and its importance. The conclusion. Tourism is considered as an economic activity and quite complex, becoming a powerful means of economic development of a country, therefore attention should be paid to global education, making the community aware of long-term sustainability and committing to international cooperation. Tourism today has grown into a special phenomenon. Based on its massiveness, it is accepted global industry. The global nature of tourism trends is expressed as the international transfer of ideas, information, capital and people of different cultures.